Clostridium difficile spore-host interactions: Defining the role of the collagen-like BclA exosporium proteins in Clostridium difficile spore-entry into intestinal epithelial cells and in the pathogenesis of the infection. - Paredes - Sabja; Daniel (2023)
PROJECT RESULTS: Describe the results of your research in reference to its original and/or modified Project objectives. The maximum extension of this section is 5 pages (Arial or Verdana font, size 10). ALL FIGURES ARE IN ANEXOS Aim 1. To determine whether the collagen-like BclA2 and/or BclA3 exosporium proteins are responsible for hair-like projections formation in C. difficile spores and interact with fibronectin and vitronectin. C. difficile spores interact with fibronectin (Fn) and vitronectin (Vn) in a dose dependent manner 1(Mora-Uribe et al. 2016. Therefore, in this aim, we first, determined whether the hair-like projections are formed by the collagen-like BclA2 and/or BclA3 proteins; next, we will characterize the interactions between the BclA proteins (i.e., BclA2 and BclA3) with Fn and Vn, and identify the domains of each protein implicated in this binding; and finally, we will explore additional ligand(s) molecule(s) and/or cellular receptors with which C. difficile BclA proteins might interact. In some experiments, we will include CdeM which is another putative spore-ligand of Fn and Vn. C. difficile spores of epidemically relevant strains exhibit hair-like projections that are likely to be formed by the collagen-like exosporium proteins2,3. Fn and Vn have a gelatin/collagen-binding domain4,5, suggesting that these molecules might interact with C. difficile spores through these hair-like projections. Indeed, through TEM coupled with immunogold labeling of Fn and Vn, we observed that more than ~50% of the spores were positive for Fn- or Vn-immunogold particles (Figure 1a,b); immunogold Fn- and Vn-specific particles were observed in proximity to the hair- like extensions of C. difficile R20291 spores (Figure 2a,b), suggesting that these structures might be implicated in spore entry into IECs. Most epidemically relevant strains encode two collagen-like exosporium proteins, BclA2 and BclA32,3. During the sporulation of R20291 strain, bclA3 expression levels are ~60-fold higher than those of bclA26. ...